Hegemoni Rezim Politik Di Ranah Lokal : Studi Kasus Di Kabupaten Pati Di Bawah Kepemimpinan Haryanto - Aninditya - Normalitasari; Laila Kholid Alfirdaus (Journal of Politic and Government Studies, 2020)
This research explains how the power of local political regimes is formed and works about the study of the Pilkada Pati Regency in 2017 of the perspective of the Power Cube theory. This research method uses the descriptive qualitative research methods in studying cases. The result of this research is about the political regimes can be formed because og the local workers presence in this region and the power of workers that cannot be separated in the bureaucracy. Formal workers such as DPR, Forkopimda, is non workers such as community and regigious leader. For this responbly it is Led by the Regent of Pati beside using his formal assignment he also use informal workers in closing place to take the authorities as the democracy symbol and to keep the sympathy and participation from the community